2018
DOI: 10.1039/c8cp04102d
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte solvents for high voltage lithium ion batteries: ion correlation and specific anion effects in adiponitrile

Abstract: Combined atomistic molecular dynamics, quantum chemical, and experimental study regarding the properties of two lithium conducting salts in high voltage electrolyte solvent adiponitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 96 publications
1
33
0
Order By: Relevance
“…In accordance, a more detailed study on the nature of the ion-solvent interactions revealed that dipolar electrostatic interactions are mainly responsible for the observed effects whereas entropic contributions in terms of solvent arrangements only account for 10-20% [15] to the ion free solvation energy, and are thus of minor importance [50]. Comparable findings were also reported for adiponitrile [74], in addition to propylene and ethylene carbonate [75], as well as for lithium salts in presence of urea [76,77].…”
Section: Molecular Properties Of the Solvent: Donor/acceptor Numbers supporting
confidence: 60%
See 1 more Smart Citation
“…In accordance, a more detailed study on the nature of the ion-solvent interactions revealed that dipolar electrostatic interactions are mainly responsible for the observed effects whereas entropic contributions in terms of solvent arrangements only account for 10-20% [15] to the ion free solvation energy, and are thus of minor importance [50]. Comparable findings were also reported for adiponitrile [74], in addition to propylene and ethylene carbonate [75], as well as for lithium salts in presence of urea [76,77].…”
Section: Molecular Properties Of the Solvent: Donor/acceptor Numbers supporting
confidence: 60%
“…With regard to this point, some ion pairs are more stable than others which also depends on the chosen solvent and further components of the solution. Corresponding experimental and simulational approaches suggested that this behavior is universal and occurs for all ions in aprotic as well as protic solvents due to different solvation interactions [18,20,34,74,[90][91][92]. Previous explanations for these effects often cite the law of matching water affinities (LMWA), which states that ion pairs with comparable water affinities reveal the highest ion pair formation stabilities [93].…”
Section: Specific Ion Effectsmentioning
confidence: 99%
“…The electrolyte 1-TFSI-E exhibits an ionic conductivity (14.1 mS cm À1 ) that is twice as high and a viscosity (2.6 mPa s) only half of the carbonate-based electrolytes, indicating that present solvents rather than the nature of the anions are responsible for the observable properties of the considered electrolyte formulations, despite that specific anion solvation effects were suggested in case of for example adiponitrile-based electrolytes. 44 Cell resistance of Li8Li coin cells in contact with the different electrolytes. The evolution of the cell resistances was monitored via electrochemical impedance spectroscopy (EIS), where the resulting resistances of the coin cells are presented in Table S1 (ESI †).…”
Section: Variation Of Conducting Salts and Solventsmentioning
confidence: 99%
“…Adiponitrile (ADN) shows the best thermal stability, low viscosity and high dielectric constant in many dinitrile-based solvents (Abu-Lebdeh and Davidson, 2009 ; Isken et al, 2011 ; Douaa et al, 2018 ). The most remarkable feature of this kind of substance is that it can still ensure that the electrolyte has an electrochemical window of about 7.0 V when used alone, and can still maintain 6.0~6.5 V in binary or ternary electrolyte (Kirshnamoorthy et al, 2018 ). Adiponitrile (ADN) has high oxidation stability under high pressure.…”
Section: Introductionmentioning
confidence: 99%